The characteristics of the strength and power at the lower extremity in the rebound jump for collegiate women soccer players: Relationship between running, strength, and difference of competition level - Yoshida, T.; Kawahara, F.; Fukuda, A.; Shirai, A.; Sakuma, A.; Zushi, A.; Asai, T.; Tanigawa, S.; Hirashima, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2021)
The present study was conducted to investigatecharacteristics of the strengthand power of thelower limb using the rebound jump (RJ) for collegiate female soccer players from the relationship with various running performance and muscular strengths and the difference in the competition level. Nineteen collegiate female soccer players performed the 20 m sprint, pro-agility, squat, isokinetic knee strength, countermovement jump, and RJ to calculate performance variables. The kinetics data (ground reaction force, joint torque, power, joint work) in the RJ were then calculated. As results, there was no relationship between the performance variables in RJ and various running performance, muscle strengths. However, in starter group, 20 m sprint time, pro-agility time was significantly faster, RJ-indexwas significantly higher, contact time in RJ was significantly shorter. In addition, in the starter group, the maximum ground reaction force, the ankle joint torque, power, and the knee joint torque in the first half of take-off phase were large. Therefore, it is suggested that female soccer players with high competition level are excellent in the strengthand powerabilities, and particularly excellent in ankle joint and knee joint muscle strength and power exertion ability to obtain jumping height in a short contact time.